Understanding the Treatment of COVID-19 and other Epidemics in Traditional Chinese Medicine - Liyun Chen; Shiyun Yan (Wolters Kluwer Health/LWW, 2020)
Epidemics spread quickly and are highly contagious. And there has been a profound understanding of etiology, pathogenesis, prevention, and treatment of these diseases in traditional Chinese medicine (TCM). Coronavirus disease 2019 (COVID-19) falls into the category of "epidemic dampness", and the core pathogenesis is that latency of externally-contracted dampness turbidity and epidemic toxin in pleurodiaphragmatic interspace provokes Shaoyang ministerial fire and causes concomitant attack of external and internal pathogens, resulting in wood fire tormenting metal and the upward rushing of dampness fire (toxin), ultimately leading to a syndrome of epidemic toxin blocking the lung. Throughout the treatment of COVID-19, Professor Shiyun Yan uses the "harmonizing" method and sticks to the basic principles of "protecting middle qi, pectoral qi and yin fluid" to consolidate the root, dispersing externally and clearing internally and using in combination drugs cold and warm in property. The specific treatment approaches include ventilating lung and expelling pathogens, clearing heat and removing the toxin, tonifying qi and nourishing yin, activating blood and resolving stasis, resolving dampness, and dredging collaterals, to prevent the patient's condition from getting worse and save the dying.